MULTILEVEL OSTEOSYNTHESIS OF THE LOWER EXTREMITIES BY THE ILIZAROV METHOD TO ELIMINATE DEFORMITIES AND SHORTENINGS IN CHILDREN AND ADOLESCENTS - Jahongirovna Mahlie Jumayeva (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
-